Dimensions of Religiosity, Mutual Cooperation, Independence, and Creativity: The Relevance of Character Education in the Novel An Episode - Wahyuni; Mukti Widayati; Suwarto (Universitas Pendidikan Ganesha, 2026)
The education paradigm in the global era reveals gaps in the implementation of character education, especially in line with the Pancasila Student Profile (PPP). This study aims to analyze the dimensions of the Pancasila Student Profile reflected in the novel Sebuah Episode by Hanum Safnas. This research is a descriptive qualitative type based on content analysis. The data are in the form of quotations (words, groups of words, or paragraphs) in the text that describe the dimensions of the Pancasila Student Profile. The data source in this study is the novel Seorang Episode. Data collection was conducted using library research methods. Sampling used a purposive technique. Data validity testing used source and theory triangulation. The data analysis techniques used were content analysis and interactive techniques. The results of the study show that the Pancasila Student Profile, faithful and devoted to God Almighty, and noble character, is represented by characters who uphold the value of religiosity. Cooperation is shown through the characters' efforts to alleviate the burdens their friends face. Independence is a role model for Pancasila students, realized through efforts to utilize time and potential, critical reasoning, and creativity, based on the persistence of the characters in proving that friendship passes many tests and must be resolved with effective solutions. This study concludes that the novel is relevant to support student character education. The implications of this study show the consistency of Pancasila students in developing all academic and non-academic potential through the representation of character education in the novel An Episode.